Hyaluronic acid in cartilage and proteoglycan aggregation - Hardingham, Timothy E. (1974)
1. Dissociation of purified proteoglycan aggregates was shown to release an interacting component of buoyant density higher than that of the glycoprotein-link fraction of Hascall & Sajdera (1969). 2. This component, which produced an increase in hydrodynamic size of proteoglycans on gel chromatography, was isolated by ECTEOLA-cellulose ion-exchange chromatography and identified as hyaluronic acid. 3. The effect of pH of extraction showed that the proportion of proteoglycan aggregates isolated from cartilage was greatest at pH4.5. 4. The proportion of proteoglycans able to interact with hyaluronic acid decreased when extracted above or below pH4.5, whereas the amount of hyaluronic acid extracted appeared constant from pH3.0 to 8.5. 5. Sequential extraction of cartilage with 0.15m-NaCl at neutral pH followed by 4m-guanidinium chloride at pH4.5 was shown to yield predominantly non-aggregated and aggregated proteoglycans respectively. 6. Most of the hyaluronic acid in cartilage, representing about 0.7% of the total uronic acid, was associated with proteoglycan aggregates. 7. The non-aggregated proteoglycans were unable to interact with hyaluronic acid and were of smaller size, lower protein content and lower keratan sulphate content than the disaggregated proteoglycans. Together with differences in amino acid composition this suggested that each type of proteoglycan contained different protein cores.